Corporate Governance, Capital Structure, Ownership Structure, And Corporate Value Of Companies Listed At The Nairobi Securities Exchange - Onguka, David; Iraya, Cyrus M.; Nyamute, Winnie L. (European Scientific Journal, ESJ, 2021)
This paper focuses on establishing the relationship among corporate governance, capital structure, ownership structure, and firm value for companies listed at the Nairobi Security Exchange (NSE). The study tested three hypotheses that explored various aspects of this relationship: First, there is no intervening effect on the capital structure on the relationship between corporate governance and corporate value; Second, there is no significant moderating effect of ownership structure on the relationship between corporate governance and corporate value; and finally, there is no significant joint effect of corporate governance, capital structure, and ownership structure on corporate value. The data of the study was obtained from audited financial statements of the firms listed at the NSE. A census survey for sixty-four publicly trading firms at the NSE was undertaken. The data of 64 corporations was cleaned, leaving a smaller number of 58 firms which formed over 90% of the sample. The analysis covered a five-year period between 2013 to 2017. The study adopted a positivism philosophy and a descriptive design. Descriptive statistics and diagnostic tests were undertaken and thereafter inferential statistics, specifically correlation and regression analysis, were used for hypothesis testing. The multiple regression analysis was used to test the relationship among corporate governance, capital structure, ownership structure, and corporate value. The panel data procedure was considered more appropriate as the sample data contained both cross-sectional and time-series data. The Baron and Kenny’s (1986) approach was used to assess the intervening and moderating effect of capital structure and ownership structure respectively on the relationship between corporate governance and corporate value. Corporate Governance was measured by a composite of board independence, board size, board remuneration, and corporate gender diversity. Capital structure was measured by leverage, while ownership structure was measured by ownership concentration, state ownership, family ownership, and foreign ownership. Firm performance was measured using the Tobin Q. The joint effect of corporate governance, capital structure, and ownership structure on corporate value was found to be positive and significant. However, Ownership structure and capital structure had no significant moderating and intervening effects respectively on the relationship between corporate governance and corporate value. This study makes an original contribution as it takes a more holistic approach of corporate governance development by probing whether improving corporate governance is linked to the enhanced corporate value. The study recommends that corporate shareholders, boards, regulators, and management of listed corporations should put in place robust policies. This will ensure the implementation and monitoring of corporate governance principles and ensure congruence in their activities of the oversight of corporate objectives of optimizing corporate value and minimizing fraud and failure risks of corporations.